1998
DOI: 10.1159/000006841
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome in Patients with Implantable Cardioverter Defibrillators

Abstract: This study determined the impact of clinical characteristics on shock occurrence and survival in patients with implantable cardioverter-defibrillator (ICD). Methods and Results: During a follow-up of 27 ± 18 months, the actuarial incidence of appropriate shocks in 200 consecutive patients was 18, 36 and 72% at 1, 3, and 5 years, respectively. Coronary artery disease was the only significant predictor for shock occurrence (relative risk 1.32, p = 0.03). The actuarial incidence of total mortality was 10, 17 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…NYHA classification also achieved a significant association with survival in univariate analysis, but not in multivariate analysis in this study. This finding was different from two studies [20,21] in which NYHA classification (worse HF) was a significant independent predictor of mortality after adjusting for the clinical and demographic predictor variables such as EF, history of coronary artery disease, VT, VF, dilated cardiomyopathy, cardiac arrest, gender, and age.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…NYHA classification also achieved a significant association with survival in univariate analysis, but not in multivariate analysis in this study. This finding was different from two studies [20,21] in which NYHA classification (worse HF) was a significant independent predictor of mortality after adjusting for the clinical and demographic predictor variables such as EF, history of coronary artery disease, VT, VF, dilated cardiomyopathy, cardiac arrest, gender, and age.…”
Section: Discussioncontrasting
confidence: 99%
“…In these studies, QOL was identified as a significant independent predictor of mortality. Previous studies of survival in ICD recipients found that EF [4,[16][17][18][19], NYHA classification [16,17,20,21], ICD shocks [20,22], gender [20], and history of sustained VT [23] predicted mortality. In this study, EF was a significant predictor in univariate analysis, however, in the multivariate analysis, EF did not have a significantly independent relationship to survival.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…11,12) Reduced left ventricular ejection fraction has been shown to increase the rate of ICD therapy delivery and mortality in several studies, 13,14) but was not predictive in others. 15,16) The time interval between myocardial infarction and device implantation may play an important role in determining which patients are at increased risk. Data from the MADIT II trial suggest that mortality risk in patients with ejection fraction 30% or lower increases as a function of time from myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%